Promoting Healthier Purchases: Ultraprocessed Food Taxes and Minimally Processed Foods Subsidies for the Low Income - Valizadeh, Pourya; Ng, Shu Wen (American journal of preventive medicine, 2024)
Fiscal policies can shift relative food prices to encourage the purchase and consumption of minimally processed foods while discouraging the purchase and consumption of unhealthy ultraprocessed foods, high in calories and nutrients of concern (sodium, sugar, and saturated fats), especially for low-income households. The 2017–2018 packaged food purchase data among U.S. households were used to derive household income- and composition-specific demand elasticities across 22 food and beverage categories. Policy simulations, conducted in 2022–2023, assessed the impact of national taxes on unhealthy ultraprocessed food and beverage purchases, both separately and alongside subsidies for minimally processed foods and beverages targeted to low-income households. Resultant nutritional implications are reported on the basis of changes in purchased calories and nutrients of concern. In addition, financial implications for both households and the federal government are projected. A sugar-based tax on sugar-sweetened beverages would lower both volume and calories purchased with the largest impact on low-income households without children. Meanwhile, targeted subsidies would increase fruit, vegetable, and healthier drink purchases without substantially increasing calories. Under tax simulations, low-income households would make larger reductions in their absolute volume and calorie purchases of taxed foods and beverages than their higher-income counterparts, suggesting that these policies, if implemented, could help narrow nutritional disparities. Levying national taxes on unhealthy ultraprocessed foods/beverages and offering targeted subsidies for minimally processed foods/beverages could promote healthier food choices among low-income households. Such policies have the potential to benefit low-income households financially and at a relatively low cost for the federal government annually.